Sistem Informasi Pemasaran Biduk Wisata Pulau Berbasis Web Mobile (Studi Kasus di Sungai Pisang, Padang, Sumatera Barat) - Elita Amrina; Insannul Kamil; Hadigufri Triha; Ardhian Agung Yulianto (Jurnal Optimasi Sistem Industri, 2019)
The geographical condition of Sungai Pisang Village located on the coastal fringe and not too far from the famous island tourism which potential in West Sumatera becomes an opportunity for the people of Sungai Pisang, especially the fishermen to increase their standard of living. But in reality, the outsiders in the Bungus area are more likely to take advantage of the opportunity because of their location close to the city center. The tourists can only be seen from afar by biduk fishermen of Sungai Pisang. Most tourists prefer to use Tour and Travel services from Bungus area. Biduk fishermen are only bringing few tourists to the island tour even though the price offered is much cheaper. Based on preliminary study, there are problems such as the lack of knowledge of the fisherman on the effective product marketing strategy. So far, there are no marketing tools to promote the transportation services of biduk fisherman to the island tourism in the Sungai Pisang broadly. Therefore, it is necessary to design a marketing information system for island tourism biduk.  The marketing information system is a mobile web-based designed using PHP programming language and supported by the MySQL database. The information marketing system is expected to increase the number of tourists who use the island tourism biduk as an effort to increase the sustainable fishermen's economy.